Feasibility study of tapioca production from dried cassava on small and medium industries - Wijana, Susinggih; Nurika, Irnia; Ningsih, ika (Jurnal Teknologi Pertanian, 2011)
The aim of this research was to find out the technical and financial feasibility ofproduced tapioca flour from cassava dried. The methods used  in this research aredescriptive and experimental. Analysis was done on the product quality, consumeracceptance test by hedonic scale (using expert panelist), and  best treatment by indexeffectivity method,  and different test between the best treatment and commercialproduct, also analysis of financial exhibit production cost and Break Event Point. Resultindicated that the best treatment  was the processing  tapioca by replacement soakingwater with value product  1,000 and average value 5,5 (like). Best product result ofassessment of consumer was included in the quality of A (middle) with tapioca flourcharacteristic was: yield 38%, water content 7,69%, starch content 76,21%, sulphiteresidual 14 ppm, ash content 0,95%, and white degree to MgSO4 was 77,49%. At theproduction capacity planned of 2,895 ton/9 months needed total cost of Rp.567.063.000,00, and at price sell of Rp. 2.749,00 /kg, yielded total of profite Rp.113.376.353,00. The value of Break Event Point (BEP)  at  volume was 18.203,88 /kg or price was  Rp. 50.042.476,00.Key word: feasibility, tapioca, dried cassava